BRANDING JURNAL KEWIRAUSAHAAN DAN BISNIS - Susantiningrum Susantiningrum; Bara Yudhistira; Dimar Hantari (Jurnal Kewirausahaan dan Bisnis, 2020)
Jurnal Kewirausahaan dan Bisnis (JKB), Entrepreneurship Development Center (PPKwu) has printed ISSN and electronic ISSN. This activity aims to improve the quality and capacity of management PPKwu, especially in managing journal towards reputable journals, such as by improving the content and appearance of the journal. The activity is carried out by applying a mixture of quantitative and qualitative methods, and by applying a comparative analysis to compare the conditions of JKB before and after the activities are carried out. By carrying out this activity it is hoped JKB can become a reputable journal and have sufficient qualifications to register for national journal accreditation. Activities that have been carried out include: a workshop to improve journal logos and headers, a workshop to improve content, DOAJ indexation, DOI repairs, workshops to improve print journal covers and brochure development.Key words: accreditation, entrepreneurship, institution, journal